Socio-Economic Transformations of Small Rural Settlements of Zakarpattia Amidst Decentralisation - Miklovda, Vasyl P.; Pitiulych, Mykhailo I.; Hoblyk, Volodymyr V.; Pityulych, Mykhaylo M.; Keretsman, Nataliya I. (International Journal of Criminology and Sociology, 2021)
The study analyses the key parameters of the population of small rural settlements of the Zakarpatska Oblast amidst economic transformation. Small settlements are described by low population density, which in some rural settlements is three times lower than the regional average. Over the last period there has been a tendency to increase the number of small rural settlements with a population of less than 150 people. Depopulation of villages creates conditions when it is unprofitable to maintain educational, healthcare, cultural institutions, etc. The current situation leads to the destruction of the infrastructure of the village, which is already in decline. The purpose of the study is to analyse the socio-economic development of small rural settlements in the region amidst decentralization. The main attention is paid to the study of problems that describe the quality of life of the rural population – analysis of the main trends of demographic reproduction, the development and effectiveness of new legal forms of management in rural areas amidst the intensifying market relations. The sectoral structure of the economy of rural settlements is analysed, the study substantiates the offers directed on integration of small rural commodity producers in the integrated agro-industrial structures, development of the rural industry, establishment of cooperative movement in the village. The level of satisfaction of the rural population with the main objects of social infrastructure is investigated on the materials of sociological monitoring of the rural population.